Perubahan Regulasi Nasional dan Efeknya Pada Investasi di Indonesia - Aryo Bimo Dewanto (LPPM Universitas Ekasakti Padang, 2023)
A country basically needs foreign investment, especially in the form of direct investment. What is often considered a crucial factor is the regulations that intersect with investment in recipient countries. Recently, however, multinational companies are also considering other rules relating to the resources they will use. This research leads to the conclusion that there is a chain effect, from a regional regulation on investment, even though the regulation does not regulate procedures, nor does it directly affect the investment climate in the receiving country.